2018
DOI: 10.1210/jc.2018-00277
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genetic Analysis of Follicular Thyroid Carcinoma Predicts Prognosis Independent of Histology

Abstract: Though the number and variety of somatic variants are similar in the different histopathological subtypes of FTC in our study, mutational burden was an independent predictor of mortality and recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 40 publications
1
44
1
1
Order By: Relevance
“…EIF1AX and GNA11/GNAQ mutations frequently co-occurred and were mutually exclusive with c-MYC amplification (16). EIF1AX mutations have been reported in benign thyroid adenomas (17) and follicular carcinomas (18), as well as in ∼1% of PTC in a mutually exclusive manner with other drivers (4). By contrast, they are present in 11% of PDTC and ATC and are almost invariably associated with oncogenic RAS (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…EIF1AX and GNA11/GNAQ mutations frequently co-occurred and were mutually exclusive with c-MYC amplification (16). EIF1AX mutations have been reported in benign thyroid adenomas (17) and follicular carcinomas (18), as well as in ∼1% of PTC in a mutually exclusive manner with other drivers (4). By contrast, they are present in 11% of PDTC and ATC and are almost invariably associated with oncogenic RAS (5,7).…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of the somatic mutation profiles among FAs and FTCs supports the point raised regarding FTCs more likely being a continuum of FAs rather than a distinct diagnostic entity and will probably add to the ongoing scientific discussion (20,21). Recent studies have explored the possible correlation of the somatic mutation signature and burden to histopathological diagnostic classes and found no substantial correlation (2,15,22,23). However, two of the studies succeeded in showing a significant correlation between patient prognosis and mutational signature and/or overall mutation load (15,23).…”
Section: Discussionmentioning
confidence: 55%
“…Recent studies have explored the possible correlation of the somatic mutation signature and burden to histopathological diagnostic classes and found no substantial correlation (2,15,22,23). However, two of the studies succeeded in showing a significant correlation between patient prognosis and mutational signature and/or overall mutation load (15,23). In brief, the study by Nicolson et al (15) correlated the somatic signature of 39 FTC to both diagnosis and prognosis and found that mutation burden was associated to a worse prognosis, independent of histopathological classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our group recently published a whole exome-sequencing analysis of FTC that mapped the genetic landscape of these tumors, with a particular emphasis on the infrequent widely invasive (WIFTC) subtype. 2 Of 10 WIFTC patients studied, 5 experienced recurrence and died of FTC within 10 years. Of 6 thyroid cancer-specific deaths in our overall FTC cohort of 39 cases, half were classified as stage I or II by the American Joint Committee on Cancer (AJCC) eighth-edition staging system, mostly due to the increased age cutoff of 55 years.…”
mentioning
confidence: 99%